2020
DOI: 10.1161/jaha.120.017502
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Amount and Pattern of Physical Activity With Arterial Stiffness: The Maastricht Study

Abstract: Background Arterial stiffness is an independent risk factor for cardiovascular disease and can be beneficially influenced by physical activity. However, it is not clear how an individual’s physical activity pattern over a week is associated with arterial stiffness. Therefore, we examined the associations of the amount and pattern of higher intensity physical activity with arterial stiffness. Methods and Results Data from the Maastricht Study (n=1699; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 35 publications
4
31
1
Order By: Relevance
“…Similarly, and in agreement with the results of this study, the benefit of physical activity on arterial stiffness was only achieved when its intensity was high [14,15,47,48]. Similarly, the recent study by Vandercappellen et al [13] reported that practicing intense physical activity was associated with lower arterial stiffness, detecting no differences among different exercise patterns; thus, they concluded that, from the perspective of arterial stiffness, performing intense physical activity, regardless of the weekly pattern conducted, can be an important strategy to reduce the risk of cardiovascular disease. Moreover, the effects on arterial stiffness vary depending on the modality of physical activity performed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, and in agreement with the results of this study, the benefit of physical activity on arterial stiffness was only achieved when its intensity was high [14,15,47,48]. Similarly, the recent study by Vandercappellen et al [13] reported that practicing intense physical activity was associated with lower arterial stiffness, detecting no differences among different exercise patterns; thus, they concluded that, from the perspective of arterial stiffness, performing intense physical activity, regardless of the weekly pattern conducted, can be an important strategy to reduce the risk of cardiovascular disease. Moreover, the effects on arterial stiffness vary depending on the modality of physical activity performed.…”
Section: Discussionsupporting
confidence: 93%
“…However, depending on the intensity and type of physical activity, and sex, its effect on arterial stiffness may vary. Thus, Vandercappellen et al [ 13 ] examined the association of the amount and pattern of intense physical activity with arterial stiffness in the Maastricht study. They reported that while a negative association between intense physical activity and arterial stiffness was found, this was not the case with regular or weekend physical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is questionable whether PA of very short duration has the same beneficial effects on patients with CVD as structured exercise. Several mechanisms may explain the known benefits associated with PA in patients with CVD, including endothelial function improvement ( 42 , 43 ) and antiatherosclerotic ( 43 , 44 ) and anti-inflammatory ( 45 ) effects. Traditional risk factors for CHD such as diabetes, hypertension, smoking, and hypercholesterolemia are associated with endothelial dysfunction, which in turn results in impaired nitric oxide production, abnormal vasoconstriction, chronic inflammation, and increased oxidative stress ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity could reduce the risk of aortic diseases because it has a beneficial effect on cardiovascular risk factors such as hypertension and arterial stiffness as well as an anti-inflammatory effect [17][18][19][20][21] . A previous meta-analysis of prospective studies suggested that higher levels of physical activity were associated with a reduced risk of aortic diseases; however, only five of nine studies showed no association, and three of five studies did not adjust for major confounders such as smoking, obesity, and hypertension 22) .…”
Section: Discussionmentioning
confidence: 99%